2006
DOI: 10.1080/13645700600836695
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical development of SMA artificial anal sphincters

Abstract: This article presents some progress in the development for preclinical trials of an artificial anal sphincter using shape memory alloys. The novel device has been proposed and developed by the author's group at Tohoku University. It has two dominant features different from other systems, which are either clinically available or still under development. One is that a solid driving element, a combination of shape memory alloy (SMA) ribbons and silicone elastomer sheets with a layered structure, is adopted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…A series of one to three months studies with goats was performed to test safety and efficacy of the pre-clinical prototype. 31 The authors had not detected any sign for infection around the implant but found a 3 to 5 mm-thick fibrous capsule around all components after 13 weeks. This capsule presumably influenced the force acting on the tissue, which was originally set to 5 to 8 kPa, i.e., 40 to 60 mmHg.…”
Section: Current Research On Artificial Sphincter Prosthesesmentioning
confidence: 87%
See 1 more Smart Citation
“…A series of one to three months studies with goats was performed to test safety and efficacy of the pre-clinical prototype. 31 The authors had not detected any sign for infection around the implant but found a 3 to 5 mm-thick fibrous capsule around all components after 13 weeks. This capsule presumably influenced the force acting on the tissue, which was originally set to 5 to 8 kPa, i.e., 40 to 60 mmHg.…”
Section: Current Research On Artificial Sphincter Prosthesesmentioning
confidence: 87%
“…To avoid thermal damages of the surrounding tissue and to allow healing after the surgery, a hinge mechanism keeps the canal open for the necessary periods of time. 31 …”
Section: Current Research On Artificial Sphincter Prosthesesmentioning
confidence: 99%
“…The research team from SEE, SJTU highly integrated all the components with sensor feedback to make surgical implantation easy and at low risk (Zan et al, 2008). Yun Luo developed an AAS device with a reduced number of parts and a compact structure for a less invasive prosthesis (Luo et al, 2006). In preliminary studies, Yun Luo found that the thickness of tissue around the implant was changed dramatically by a stress shielding effect caused by the large mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The basic design of the device is to use two elements implanted inside the body: an SMA based artificial sphincter and a secondary coil (Fig. 5) (Luo et al, 2006). Although the dimensions of the artificial sphincter are comparable to those of the silicone cuff in the AMS800, the secondary coil is disk-like and drastically reduces the volume of the implant.…”
Section: Tohoku University Artificial Sphincter Systemmentioning
confidence: 99%
“…Thus, stable and implantable PSS is required to supply enough power to AAS. Therefore, some preliminary form of PSSs appear in later AAS like Acticon Neosphincter, PAS, GASS, and artificial sphincter-shape memory alloy (AS-SMA) [17][18][19][20][21][22][23] . Preliminary PSSs bring many advantages to AAS.…”
Section: Introductionmentioning
confidence: 99%